(untitled) (Physical Education, Health and Social Sciences, 2025)
Purpose: The purpose of the present study was to assess differences in the pragmatic language skills of children with Down syndrome and typically developing children. Method: 60 Children with mental age 5.0-6.0 were recruited for both groups (Down syndrome=30, typically developing children=30). Non probability purposive sampling was employed and data was collected from special education schools. Demographic sheet and Orion’s Pragmatic Language Skills Questionnaire (OPLS) consisting of nonverbal communication, expressive skills, conversational skills, speech conventions and peer skills was used for pre and post assessment. Results: Data was analyzed statistically. The results shows statistically significant difference between pragmatic language skills of children with down syndrome and typically developing children (NVC= t(58)=2.14, p>0.03, ES= t(58)=-5.47, p>0.001, CSTM= t(58)=-8.32, p>0.001, CSTT= t(58)=-6.32, p>0.001, SC= t(58)=-4.21, p>0.001, PS= t(58)=-5.43, p>0.001, O= t(58)= -7.16, p>0.001). Conclusion: It was concluded that nonverbal communication skills were stronger in Children with Down syndrome then typically developing children